Utilizing IPFS for Decentralized Data Storage a Security and Censorship Resistance Solution - Herman Herman; Willya Achmad; Nur Aulia; Suca Rusdian; Thomas Green (IAIC Bangun Bangsa, 2026)
This study explores the InterPlanetary File System (IPFS) as a decentralized storage solution aimed at reducing dependence on centralized cloud systems. The research analyzes how the integration of IPFS with blockchain and smart contracts can enhance data security, maintain data availability, and minimize censorship risks in digital environments. This topic is relevant because centralized storage still places control in a single point, creating vulnerabilities to cyberattacks, unauthorized access, and failures caused by system dependency. Although several studies have discussed IPFS in different contexts, there is a clear gap in the absence of a structured comparative explanation showing how IPFS, blockchain, and smart contracts operate together in decentralized data governance. Using a qualitative literature review from reputable academic sources, this study synthesizes existing findings into a clearer conceptual mapping. The novelty lies in the development of a comparative matrix that unifies previous technical insights, providing a more accessible understanding of how decentralized technologies support secure and censorship-resistant data ecosystems. The results indicate that IPFS preserves data authenticity through cryptographic hashing, improves data availability through distributed replication, and reduces censorship risks because access does not depend on a central authority. However, several challenges remain, including latency, uneven node distribution, and the difficulty of fully removing stored data. Overall, the study concludes that IPFS shows strong potential for future digital infrastructure, yet its adoption requires strategic planning, supportive policies, and gradual implementation to ensure sustainability and operational effectiveness across diverse technological environments.